Platelet Activation Assessed by Glycoprotein VI/Platelet Ratio Is Associated With Portal Vein Thrombosis After Hepatectomy and Splenectomy in Patients With Liver Cirrhosis. (March 2018) - Matsui, Toshiki; Usui, Masanobu; Wada, Hideo; Iizawa, Yusuke; Kato, Hiroyuki; Tanemura, Akihiro; Murata, Yasuhiro; Kuriyama, Naohisa; Kishiwada, Masashi; Mizuno, Shugo; Sakurai, Hiroyuki; Isaji, Shuji
Portal vein thrombosis (PVT) is a serious complication after hepatobiliary-pancreatic surgery. Portal vein thrombosis often develops in patients with liver cirrhosis (LC) postoperatively, although they have low platelet counts. Platelet activation is one of the causes of thrombosis formation, and soluble form of glycoprotein VI (sGPVI) has received attention as a platelet activation marker. We had prospectively enrolled the 81 consecutive patients who underwent splenectomy (Sx) and/or hepatectomy: these patients were divided as Sx (n = 38) and hepatectomy (Hx, n = 46) groups. The 3 patients who underwent both procedures were added to both groups. Each group was subdivided into patients with non-LC and LC: non-LC-Sx (n = 22) and LC-Sx (n = 16), non-LC-Hx (n = 40) and LC-Hx (n = 6). The presence of PVT was diagnosed by using enhanced computed tomography (CT) scan. Platelet counts were significantly lower in LC-Sx than in non-LC-Sx, and incidence of PVT was significantly higher in LC-Sx than in non-LC-Sx (68.8% vs 31.8%, P = .024). Soluble form of glycoprotein VI /platelet ratios on preoperative day and postoperative day 1 were significantly higher in LC-Sx than in non-LC-Sx. Incidence of PVT was significantly higher in LC-Hx than in non-LC-Hx (50.0% vs 7.5%, P < .01). Soluble form of glycoprotein VI /platelet ratios were significantly higher in LC-Hx before and after Hx, compared to non-LC-Hx. Patients with LC stay in hypercoagulable state together with platelet activation before and after surgery. Under this circumstance, alteration of portal venous blood flow after Sx or Hx is likely to cause PVT in patients with LC.